The acute effects of boxing-specific dumbbell activity on punch performance in male amateur boxers - Jin, Rangxi; Huang, Muyun; Yi, Wenjuan; Finlay, Mitchell James; Chen, Chao (Frontiers in Physiology, 2025)
This study aimed to investigate and compare the acute effects of Dumbbell Throw (DBT) and Dumbbell Push (DBP) as punch-specific conditioning activities on subsequent punch performance in male amateur boxers, based on the post-activation performance enhancement (PAPE) framework. Eighteen participants completed maximal straight punch tests before and after conditioning activities (CA) performed with 2%, 5%, and 8% of 5RM bench press loads at 4, 8, 12, and 16 min post-CA. Punch velocity and power were measured using StrikeTec sensors. Significant CA × time interactions were observed for rear hand straight punches, with the 8% DBT condition producing peak velocity (9.81 m/s), power (29,824 W), and force (3,032 N) at 12 min post-CA. Compared to DBP, DBT led to greater improvements in rear fist velocity (+1.31 m/s, g = 1.57) and power (+6,154 W, g = 1.50). Jab performance peaked at 8 min post-CA with 5% DBT. Time main effects indicated overall enhancements. These findings suggest that DBT provides superior acute improvements in punch performance, likely due to its biomechanical specificity and stronger PAPE response. The optimal recovery time was identified as 8–12 min. Future research should include a control condition and further validate sensor-based measurements, while exploring optimal loading strategies.